2013
DOI: 10.4103/0259-1162.123238
|View full text |Cite
|
Sign up to set email alerts
|

Paravertebral block is a proper alternative anesthesia for outpatient lithotripsy

Abstract: Context:This study evaluated the effectiveness of paravertebral block as an alternative anesthetic technique for extracorporeal shock wave lithotripsy (ESWL) procedure. A total of 50 patients with renal stones, aged 20-60 years, were randomly allocated into two groups; 25 patients in group P; received unilateral paravertebral block from T8 through L1 with injection of 5 mL 0.5% bupivacaine and 25 patients in group L; received local infiltration by bupivacaine 0.25% (2 mg/kg) into the 30 cm2 area after localizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…Seven of these used a pre-specified distance beyond the transverse process as their endpoint for injection, [17][18][19][20][21][22][23] six studies reported using loss-of-resistance as their endpoint, [24][25][26][27][28][29] and four used a peripheral nerve stimulator to confirm entry into the paravertebral space. [30][31][32][33] Three studies used an ultrasound-guided technique to perform TPVB. [34][35][36] Eight studies performed TPVB injections at a single intervertebral 18 19 24-27 34 36 and 12 studies did so at multiple levels.…”
Section: Technical Performancementioning
confidence: 99%
See 3 more Smart Citations
“…Seven of these used a pre-specified distance beyond the transverse process as their endpoint for injection, [17][18][19][20][21][22][23] six studies reported using loss-of-resistance as their endpoint, [24][25][26][27][28][29] and four used a peripheral nerve stimulator to confirm entry into the paravertebral space. [30][31][32][33] Three studies used an ultrasound-guided technique to perform TPVB. [34][35][36] Eight studies performed TPVB injections at a single intervertebral 18 19 24-27 34 36 and 12 studies did so at multiple levels.…”
Section: Technical Performancementioning
confidence: 99%
“…19 Type of surgery Nine types of surgical procedure in the included studies were identified and distributed as follows: eight studies in open inguinal herniorrhaphy 17 21-24 28 32 36 ; three studies in percutaneous nephrolithotomy (PCNL) 19 20 25 ; two studies in open renal surgery 26 34 ; two studies in laparoscopic cholecystectomy 30 31 ; and one study each in open cholecystectomy, 27 donor hepatectomy, 18 ventral wall hernia repair, 29 open major gynaecological surgery 35 and extracorporeal shock wave lithotripsy (ESWL). 33 Anaesthesia vs analgesia Nine studies used TPVB as the primary anaesthetic technique. 17 22-25 28 29 33 36 In the other 11 studies TPVB was used in the intervention group solely to provide perioperative analgesia.…”
Section: Technical Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Also EL Hennawy et al, when added dexmedetomidine to caudal Bupivacaine [10]. They found that dexmedetomidine promots the analgesic time with median 16(14-18) against bupivacaine alone median 5 (4)(5)(6). This could be explained by that dexamedetomidine had both peripheral and central analgesic effects.…”
Section: Discussionmentioning
confidence: 98%